DISTRIBUSI VEKTOR DAN POTENSI PENULARAN MALARIA DI PAPUA BARAT PADA BERBAGAI EKOSISTEM - Riyani Setiyaningsih; Mega Tyas Prihatin; Mujiyono Mujiyono; Triwibowo Ambar Garjito; Widiarti Widiarti (Balai Besar Penelitian dan Pengembangan Vektor dan Reservoir Penyakit (B2P2VRP) Salatiga, 2018)
Anopheles farauti, Anopheles brancofti, Anopheles punctulatus, and Anopheles koliensis are confirmed as malaria vectors in West Papua. The distribution of vectors and their potency as malaria transmission differs in each ecosystem. The aim of this research was to investigate the distribution of vectors and their potency as malaria transmission found in various ecosystem. Mosquitoes were caught by human landing collection method, Animal-Baited Trap, and livestock-baited trap. The larval surveillance was conducted in places that have potential as breeding place for Anopheles spp. Sampling sites were conducted in Manokwari, Fak-fak and Raja Ampat districts. Each District of mosquito and larva fishing is conducted in forest ecosystem near settlement, remote forest settlement, non forest near settlement, non forest remote settlement, beach near settlement and coastal remote settlement. The result of the study demonstrated that An. farauti, An. longirostris and An. punctulatus were positive from plasmodium caught in the beach near settlement, in the remote forest settlement and in non-forest near settlement ecosystems of Manokwari Regency, respectively. Anopheles farauti caught in non-forest near settlement ecosystem of Raja Ampat Regency was also found to be positive from plasmodium. However, none mosquitoes and larvae caught in Fak-fak Regency was positive. It is concluded that those mosquitoes caught in Manokwari and Raja Ampat Regency might act as vectors of Malaria.